The Environmental Conservation: An Ecopedagogical Approach Practiced by Pesantren Annuqayah, Madura - Fawaid, Achmad (DINIKA : Academic Journal of Islamic Studies, 2016)
The massive use of plastic in the society indicated the highly unawareness of ecological impacts from the hazard. Pesantren as one of the important institution in Indonesia has a big role to the ground of the ecological knowledge to raise peopleâs environmental awareness. Pesantren Annuqayah, Madura, East Java has advocating and raising environmental awareness of the people surroundings through the activitiesâ against plastic rubbish. Ecopedagogy has been used by pesantren to raise peopleâs awareness. It is an ecoliteracy, in which the volunteer from the pesantren involved to literate local people about the dangerous effect of plastic rubbish and the importance of environmental conservation. For this reason, education is central point in which human be able to learn the importance of nature and their companionship with the earth. Human ecology is part of whole ecosystem in the world. By grounding ecopedagogy, pesantren Annuqayah has been implementing the Prophet Muhammadâs saying about environment, Alnadhofah min Aliman, into the practical level. They have successfully managed many contributive programs, such as using local materials to respect biodiversity in their areas, and managing socialization of ecological knowledge either to its students or to the communitiesâ surrounding.Keywords:Ecopedagogy, pesantren, and environmental conservation